If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 = 9x + -1(5 + -2x) Reorder the terms: 5 + 3x = 9x + -1(5 + -2x) 5 + 3x = 9x + (5 * -1 + -2x * -1) 5 + 3x = 9x + (-5 + 2x) Reorder the terms: 5 + 3x = -5 + 9x + 2x Combine like terms: 9x + 2x = 11x 5 + 3x = -5 + 11x Solving 5 + 3x = -5 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 5 + 3x + -11x = -5 + 11x + -11x Combine like terms: 3x + -11x = -8x 5 + -8x = -5 + 11x + -11x Combine like terms: 11x + -11x = 0 5 + -8x = -5 + 0 5 + -8x = -5 Add '-5' to each side of the equation. 5 + -5 + -8x = -5 + -5 Combine like terms: 5 + -5 = 0 0 + -8x = -5 + -5 -8x = -5 + -5 Combine like terms: -5 + -5 = -10 -8x = -10 Divide each side by '-8'. x = 1.25 Simplifying x = 1.25
| x-(3x+1)=2x-(4x+3)-x | | 7p+12=13+6p | | 12-4x-x^2=36-16x^2+16 | | 2+10= | | -5.2x-3.3=22.7 | | 10y+2=7 | | 2*d=5d | | 4[-2(4x+3)+2(5x-5)]= | | 9y+(-3y-5)=4y-7 | | 2m(4m)= | | 2m(11n)= | | 2m(11n+3)= | | 0.4x+5.2=4.6 | | 9(2x-4)=3(6x+1) | | x^2-11x-7=0 | | 4t+3=2t+11 | | 4-9x=-11x | | 3-(x-1)=x+2 | | 12-3x=8x+2 | | 4+8x+25-5y=23 | | 103-7x=11x+23 | | 5-(x-7)=x-4 | | 7-7x=57-21x | | X^3-6x^2+8x-2=0 | | 11x+3=2(5x-1)+5 | | 0=2x-16 | | 0.4x+4.4=3.8 | | 0=-x+15 | | o=-x+15 | | 10-2(2-x)=18 | | x+4+3+x-2+x^2+2x+3x-4=30 | | (x+7)(x+9)=2x+62 |